Single-Stage Cartilage Repair Using Platelet-Rich Fibrin Scaffolds With Autologous Cartilaginous Grafts. (November 2017) - Wong, Chin-Chean; Chen, Chih-Hwa; Chan, Wing P.; Chiu, Li-Hsuan; Ho, Wei-Pin; Hsieh, Fon-Jou; Chen, You-Tzung; Yang, Tsung-Lin
Background: To avoid complicated procedures requiring in vitro chondrocyte expansion for cartilage repair, the development of a culture-free, 1-stage approach combining platelet-rich fibrin (PRF) and autologous cartilage grafts may be the solution. Purpose: To develop a feasible 1-step procedure to combine PRF and autologous cartilage grafts for articular chondral defects. Study Design: Controlled laboratory study Methods: The chemotactic effects of PRF on chondrocytes harvested from the primary culture of rabbit cartilage were evaluated in vitro and ex vivo. The rabbit chondrocytes were cultured with different concentrations of PRF media and evaluated for their cell proliferation, chondrogenic gene expression, cell viability, and extracellular matrix synthesis abilities. For the in vivo study, the chondral defects were created on established animal models of rabbits. The gross anatomy, histology, and objective scores were evaluated to validate the treatment results. Results: PRF improved the chemotaxis, proliferation, and viability of the cultured chondrocytes. The gene expression of the chondrogenic markers, including type II collagen and aggrecan, revealed that PRF induced the chondrogenic differentiation of cultured chondrocytes. PRF increased the formation and deposition of the cartilaginous matrix produced by cultured chondrocytes. The efficacy of PRF on cell viability was comparable with that of fetal bovine serum. In animal disease models, morphologic, histological, and objectively quantitative evaluation demonstrated that PRF combined with cartilage granules was feasible in facilitating chondral repair. Conclusion: PRF enhances the migration, proliferation, viability, and differentiation of chondrocytes, thus showing an appealing capacity for cartilage repair. The data altogether provide evidence to confirm the feasibility of 1-stage, culture-free method of combining PRF and autologous cartilage graft for repairing articular chondral defects. Clinical Relevance: The single-stage, culture-free method of combining PRF and autologous cartilage is useful for repairing articular chondral defects. These advantages benefit clinical translation by simplifying and potentiating the efficacy of autologous cartilage transplantation.